Laparoscopic right hepatectomy after radioembolization using yttrium-90 resin microspheres. (March 2017) - Rotellar, Fernando; Zozaya, Gabriel; Martí-Cruchaga, Pablo; Pardo, Fernando
Abstract: Background: Liver surgery after selective internal radiation therapy (SIRT) has been scarcely reported. The combination of laparoscopic approach in post-SIRT major liver surgery is a complex scenario to our knowledge not reported so far. Method: From July' 2007–July' 2016, 40 patients underwent post-SIRT R0 resections in our center: 30 resections and 10 liver transplants. From March'2011, 5 (out of those 30) were full-laparoscopic resections: Three patients underwent laparoscopic right hepatectomy (LRH) after previous right hemiliver radiation lobectomy: two cirrhotic patients with HCC and one with colorectal cancer liver metastasis; one segment-VI resection in a cirrhotic patient, due to HCC and finally, a patient with a Budd-Chiari Syndrome and an infiltrating HCC in segment-III underwent left lateral seccionectomy. In all cases, the procedure was uneventfully completed full-laparoscopic and none required transfusion. Hospital stay was 3, 2, 5, 3 and 3 days respectively. We herein present a LRH in a 71 year-old patient after right hemiliver radiation lobectomy (due to a 7 cm unresectable HCC in a HCV cirrhotic liver). Case presentation, surgical findings and technique are detailed in this video, which also demonstrates the comparative hypoperfusion of the treated hemiliver revealed with ICG fluorescence, a hitherto undescribed finding. Results: Hospital stay was 3 days. No early or late morbidity occurred. At this writing, 18 months after the resection and 43 months after the initial diagnosis the patient is alive and free of disease. Conclusion: This experience suggests that laparoscopic liver resection after SIRT is feasible and safe, even in major hepatectomies. Highlights: We present a laparoscopic right hepatectomy in a cirrhotic patient with an initially unresectable hepatocellular carcinoma. SIRT treatment controlled the tumoral disease, but also promoted a dramatic atrophy of the right hemiliver. The compensatory increase of the left liver (turning from 30% to 70% of the total volume) allowed for a right hepatectomy. The video demonstrates how a laparoscopic approach is feasible in mayor hepatectomies after SIRT. Indocyanine Green Fluorescence revealed the hypoperfusion of the radioembolized hemiliver, a hitherto undescribed finding.